The advertisement call of the rare casque-headed frog Nyctimantis galeata (Anura: Hylidae) from its type locality, Morro do Chapéu, Bahia, Brazil - Dias, Iuri Ribeiro; Silva, Giovanni Tanajura; Solé, Mirco; de Mira-Mendes, Caio Vinicius (Zootaxa, 2020)
Nyctimantis Boulenger, 1882 was considered a monotypic genus for over a century. In a recent phylogenetic analysis of the Lophyohylini tribe with more than 96% of its representatives, Nyctimantis was redefined with the well-supported inclusion of some species from the genus Aparasphenodon, Argenteohyla and Corythomantis (Blotto et al. 2020). Therefore, the genus Nyctimantis currently consists of seven described species: N. arapapa (Pimenta, Napoli & Haddad, 2009); N. bokermanni (Pombal, 1993); N. brunoi (Miranda-Ribeiro, 1920); N. galeata (Pombal, Menezes, Fontes, Nunes, Rocha & Van Sluys, 2012); N. pomba (Assis, Santana, Silva, Quintela & Feio, 2013); N. rugiceps Boulenger (1882) and N. siemersi (Mertens, 1937).